2019
DOI: 10.1016/j.gpb.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis of CAR-T Cell Activation Reveals A Mixed TH1/TH2 Response Independent of Differentiation

Abstract: The activation mechanism of chimeric antigen receptor (CAR)-engineered T cells may differ substantially from T cells carrying native T cell receptor, but this difference remains poorly understood. We present the first comprehensive portrait of single-cell level transcriptional and cytokine signatures of anti-CD19/4-1BB/CD28/CD3ζ CAR-T cells upon antigen-specific stimulation. Both CD4 + helper T (T H ) cells and CD8 + cy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 47 publications
(73 reference statements)
2
81
1
2
Order By: Relevance
“…Although cytotoxic CD8(+) T cells mediate direct tumor cell killing, CD4(+) T helper (TH) cells are also important in tumor cell eradication [ 47 ], as CD4(+) CAR T cells exert significant cytotoxicity comparable to CD8(+) CAR T cells [ 48 ]. According to recently published single-cell analysis data, both CD4(+) TH cells and CD8(+) cytotoxic T cells are equally effective in direct tumor cell killing, and their cytotoxicity is associated with both TH1 and TH2 cytokines, e.g., IFN-γ, TNF-α, IL-15, and IL-13, as confirmed by the expression of master transcription factor genes TBX21 and GATA3 [ 49 , 50 ]. In addition, rather than stringent TH1 or TH2 subtypes, the predominant anti-tumor response is dependent on a highly mixed TH1/TH2 function in the same cell, suggesting the activation of BsAb-directed T cells or CAR T cells is a canonical process that leads to a mixed response combining both TH1 and TH2 cytokines together with GM-CSF [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although cytotoxic CD8(+) T cells mediate direct tumor cell killing, CD4(+) T helper (TH) cells are also important in tumor cell eradication [ 47 ], as CD4(+) CAR T cells exert significant cytotoxicity comparable to CD8(+) CAR T cells [ 48 ]. According to recently published single-cell analysis data, both CD4(+) TH cells and CD8(+) cytotoxic T cells are equally effective in direct tumor cell killing, and their cytotoxicity is associated with both TH1 and TH2 cytokines, e.g., IFN-γ, TNF-α, IL-15, and IL-13, as confirmed by the expression of master transcription factor genes TBX21 and GATA3 [ 49 , 50 ]. In addition, rather than stringent TH1 or TH2 subtypes, the predominant anti-tumor response is dependent on a highly mixed TH1/TH2 function in the same cell, suggesting the activation of BsAb-directed T cells or CAR T cells is a canonical process that leads to a mixed response combining both TH1 and TH2 cytokines together with GM-CSF [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…37,[45][46][47][48][49] CD28 and 41BB co-stimulation in the context of CAR T cells has been extensively studied, including detailed phosphoproteomic and single-cell RNA sequencing (RNA-seq) analyses. [50][51][52] They activate different pathways within T cells, with CD28 signaling promoting glycolytic metabolism and an effector memory phenotype, in contrast to 41BB signaling, which induces oxidative metabolism and a central memory phenotype. 53 Depending on the number of co-stimulatory molecules included in the CAR signaling domain, CARs are either designated second (one domain) or third (two domains) generation.…”
Section: Design Of Carsmentioning
confidence: 99%
“…In a recent study, TCR-seq, integration site analysis, and scRNA-seq were used to profile anti-CD19 CAR-T cells before and after infusion, revealing that clonal diversity declines following infusion and that expanding clones have higher expression of proliferation and cytotoxicity genes (54). By analyzing the transcriptional and cytokine signatures (by means of scRNA-seq and single-cell multiplex cytokine secretion assay), together with live cell imaging of cytotoxic activity, Xhangolli et al demonstrated that anti-CD19 CAR-T cells display a highly mixed Th1/ Th2 function upon antigen-specific stimulation (55). Lymphodepleting chemotherapy is routinely administered prior to CAR-T cell infusion, and has been associated with improved in vivo cell expansion and persistence (56).…”
Section: Systems Immunology and Biomarker Discovery In Patients Treatmentioning
confidence: 99%